Decomposition of Energy Intensity in the Iranian Manufacturing Industries - Alimorad Sharifi; Mehdi Sadeghi; Mahdi Nafar; zahra dehghan shabani (فصلنامه پژوهش‌های اقتصادی ایران, 2008)
In this paper, we study the factors affecting changes in energy intensity in Iran. We use Fisher Ideal index in order to decompose the energy intensity into the structural changes and efficiency improvements in the Iranian manufacturing industries during 1993-2004. The results show that the structural changes have had a little effect in decreasing the energy intensity in the manufacturing industries in Iran.